Industrial symbiosis in European policy: overview of recent progress - Katarína Petríková; Kamila Borseková; Inna Blam (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The aim of the paper is to explain the cooperation and processes realized within the industrial networks based on the principles of industrial symbiosis in Denmark, Russia and Slovakia. The identified examples can be characterized as best practices in the field of industrial symbiosis that influences importantly the development of regions, where they are localized. Industrial symbiosis as a voluntary cooperation of enterprises with the aim to optimize production costs and improve the environment could influence positively the development of areas where the companies are operating. The paper includes three examples of ‘best practices’ from Denmark, Russia and Slovakia. The examples refer the wide range of benefits that this kind of cooperation brings.